Family involvement in Peruvian school education - Sucari, Wilson (2020)
The research focused on understanding the current situation of family participation in Peruvian school education, for which different laws related to family participation in school education were analyzed and systematized. In the same way, to explain the current conditions of family participation, different reports and researches carried out about it in the educational institutions of Peru were studied. The study focused on five dimensions: the family as a facilitator of basic conditions for the schooling of children, communication between family and school, the family as a mediator in the academic learning of children, participation in management and school activities and, finally, collaboration with the community. Finally, a comparison was made between what the dimensions of family participation say with Peruvian legislation and with the practice of family participation in educational institutions.